EFFECTIVENESS OF USING PIONEER AS A REINFORCE LAYER SUBSTITUTE ON KURAU NET SHIP IN PAMBANG COASTAL VILLAGE, BENGKALIS REGENCY, RIAU PROVINCE - putra, Guspa serawal; Syaifuddin, Syaifuddin; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT                This research was conducted in August 2020 in Pambang Pesisir Village, Bantan District, Bengkalis Regency, Riau Province. The method used is an experimental method by making specimens from wood specimens without lamination and with Pioneer Non-SAG Epoxy and Fiberglass laminates. The purpose of this study was to analyze the effectiveness of using Pioneer Non-SAG Epoxy as a substitute for CSM and Wovin Roving on the ship's hull through destructive testing (DT/Destructive Test).            From the test results, the highest wood moisture content was 18.18% and the lowest value was 13. 15%, the highest density value was 1.15 g/cm3 and the lowest value was 1.02 g/cm3. Comparison of the results of the mechanical test against the bending/compression test on specimens that were coated with Pioneer, Fiber and uncoated wood from the results of the fiber coating research will increase the thickness of the wood by 4 mm (from 6 mm to 10 mm), while the pioneer coating only adds 1 mm ( from 6mm to 7mm). For this reason, if you increase the thickness of the pioneer coated wood, it is necessary to use a pioneer layer of more than 8 layers. With a thickness ratio for fiber 0.5mm and pioneer 0.125mm.            Tensile tests on fiber-coated wood are longer than pioneer-coated wood. The tensile strength of wood coated with fiber reaches 306.99 MPa while pioneer coated wood is only 230.22 MPa. The difference in the increase in the length of the wood when it is pulled is due to the difference in the thickness of the elasticity and the thickness of the wood.            Based on the impact results, it can be seen that the best value is the lowest wood with fiber coated wood with a value of 0.000054 J/mm2 and uncoated wood with a value of 0.00083 J/mm2 and the highest value is found in wood coated with Pioner with a value of 0.00083 J/mm2. 0.000094 J/mm2. Thus it can be concluded that the use of various types of layers on wood will affect the impact value.Keywords: Piooner, Physical test, Statistical test, Mechanical test